If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4 + c) = 5(c + 2) (4 * 6 + c * 6) = 5(c + 2) (24 + 6c) = 5(c + 2) Reorder the terms: 24 + 6c = 5(2 + c) 24 + 6c = (2 * 5 + c * 5) 24 + 6c = (10 + 5c) Solving 24 + 6c = 10 + 5c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5c' to each side of the equation. 24 + 6c + -5c = 10 + 5c + -5c Combine like terms: 6c + -5c = 1c 24 + 1c = 10 + 5c + -5c Combine like terms: 5c + -5c = 0 24 + 1c = 10 + 0 24 + 1c = 10 Add '-24' to each side of the equation. 24 + -24 + 1c = 10 + -24 Combine like terms: 24 + -24 = 0 0 + 1c = 10 + -24 1c = 10 + -24 Combine like terms: 10 + -24 = -14 1c = -14 Divide each side by '1'. c = -14 Simplifying c = -14
| x-.75x=165 | | 6(x-8)=-108 | | x-.34x=36000 | | 2(x-(4x+11)+3)=2(x+8) | | T+3+2T=2(T+6) | | 16t^2-16t+96=0 | | 2x+11y=2(x+3x)-47y | | 4j-5=17 | | z/3+43=70 | | 2x^2-8z=0 | | X^2+10x-19=5 | | 5/8=40/n | | 2x+3+3x-8=180 | | x=2+7y | | -83=2v-15v-18 | | 5/140=12/x | | 11/12k=1/15-13/14 | | 2x-1y=2x+10 | | 6(4-x)+3x=9 | | 7/84=12/x | | 2.5/0.6=165/n | | x=11+2(4-2(3+6)) | | Log(6)(5x+1)=2 | | 1.2/2.8=n/32 | | 32-4x=3x+9 | | x=2/7=5 | | 2y^2+3=-7y | | 16*(x^2-36)/x=0 | | -12z=4 | | 4 = -12z | | 146000000/1.18=1.18N/1.18 | | x+x*.20=100800 |